Evaluation of thermotolerant coliforms in the waters of Vigário-Campelo-Cataia System in Baixada Campista, RJ - Coelho, Alana de Azeredo (2015)
The study evaluates the concentration of thermotolerant coliforms in Vigário-Campelo-Cataia System, Baixada Campista, RJ, to contribute to the analysis of potential environmental impacts developed on this site. There were monitored seven points by collecting water samples between November 2013 and December 2014, bringing together six samples for each point. The results were satisfactory when analyzed according to the parameters set by CONAMA Resolution No. 357/2005, and it may be concluded that the atypical coliform levels presented may result from inadequate sanitation in neighborhoods like Parque Prazeres and lower rainfall at certain times.